2017
DOI: 10.1371/journal.pone.0176187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mature soybean pods as a food source for two pod-sucking bugs, Riptortus pedestris (Hemiptera: Alydidae) and Halyomorpha halys (Hemiptera: Pentatomidae)

Abstract: Riptortus pedestris (Fabricius) and Halyomorpha halys (Stål) cause injury to soybeans by piercing and sucking pods and seeds. Growers believe that new damage decreases near to harvest despite the occurrence of these bugs at that time. As this question has never been assessed, we evaluated two diets: a) mature soybean pods (dried shell + dried soybean seeds) and b) dried soybean seeds for the two bugs by assessing their biological, behavioral, and morphological attributes on each diet in laboratory. While nymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…pedestris was identified as B . bassiana and designated as strain ARP14, based on morphology [ 2 , 34 ] and intraspecies and interspecies divergence rate with different Beauveria species and strains [ 35 ]. Strain ARP14 showed high virulence to R .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pedestris was identified as B . bassiana and designated as strain ARP14, based on morphology [ 2 , 34 ] and intraspecies and interspecies divergence rate with different Beauveria species and strains [ 35 ]. Strain ARP14 showed high virulence to R .…”
Section: Discussionmentioning
confidence: 99%
“…Pod sucking bugs, including Riptortus pedestris (F.) (Hemiptera: Alydidae), Halyomorpha halys (Stål) (Hemiptera: Pentatomidae), and Nezara antennata Scott (Hemiptera: Pentatomidae), are major pests of soybean by reducing seed quality and yield [ 1 , 2 ]. Among these bugs, R .…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, pod-sucking pests are considered more important than other pod-attacking pests complex, because it has a widespread area, even during the rainy and dry season. In Bangladesh, it was also reported that these types of pod sucking pest, Riptortus pedestris (Fabricius) & Halyomorpha halys (Stal) were also major pod pests on soybean plants (Rahman & Lim, 2017). Losses in crop yields due to pod-sucking pest infestations not only reduce the productivity per unit area, but also reduced the seed vigor (Bae et al, 2014) as a result of imperfect seed formation or seed damage.…”
Section: Methods Introductionmentioning
confidence: 99%
“…It has been reported that the bean bug is the major insect pest responsible for staygreen syndrome, which is characterized by a lack of timely leaf senescence and an increase in seed abortion, in Chinese soybean fields (Li et al 2019). Many published studies have demonstrated the effects of temperature on demographic characteristics and population parameters of R. pedestris (Ahn et al 2019; Kim et al 2009; Rahman & Lim 2017). However, there are few studies regarding the direct effects of elevated CO 2 on herbivores (Akbar et al 2016; Choi et al 2018; Liu et al 2017; Xie et al 2015) and there is no information on its effects on R. pedestris .…”
Section: Introductionmentioning
confidence: 99%